Lightweight heat-insulating castable for coke oven observation hole cover and preparation and use methods of lightweight heat-insulating castable

By using lightweight thermal insulation castables, including main materials, bonding agents and pore-making agents with specific ratios, the heat dissipation problem caused by the high thermal conductivity of cast iron materials in the existing coke oven fire-hole cover is solved, and lower thermal conductivity is achieved Coefficient and higher energy saving effects.

CN119431005APending Publication Date: 2025-02-14SD STEEL RIZHAO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411687938.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The cast iron material of the existing coke oven fire hole cover has a large thermal conductivity, which leads to a large amount of heat dissipation, causing energy waste and deteriorating the furnace roof operation environment.

Method used

A lightweight thermal insulation castable is used, including main materials (calcium hexaluminate, mullite, blue crystal, etc.) and pore-forming agent (AC foaming agent), and binding agent (magnesium chloride and PVAC) to form low thermal conductivity The coefficient of fire hole cover.

Benefits of technology

The surface temperature of the fire-viewing hole cover is significantly reduced, from above 230℃ to below 70℃, reducing the heat loss inside the coke oven, and reducing the weight and cost of the fire-viewing hole cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150113070000041
    Figure BDA0005150113070000041
  • Figure BDA0005150113070000042
    Figure BDA0005150113070000042
  • Figure BDA0005150113070000043
    Figure BDA0005150113070000043
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials for coke ovens in the iron and steel industry, and particularly discloses a light heat-preservation castable for a coke oven observation hole cover and a preparation and use method thereof.The light heat-preservation castable comprises main materials, a binding agent and a pore forming agent, the main materials comprise calcium hexaluminate, mullite, kyanite, high bauxite, zirconite, high-boron calcium borate and SnO2, the binding agent comprises magnesium chloride and PVAC, and the pore forming agent is a mixture of magnesium chloride and PVAC; the pore-forming agent adopts an AC foaming agent; the preparation method comprises the following steps: weighing raw material components of the main material, the binding agent and the pore-forming agent in proportion, and mixing and stirring for 6-10 minutes; adding water accounting for 10-15% of the total weight of the mixture, and continuously mixing and stirring for 7-9 minutes to prepare a castable; pouring a castable into the fixed observation hole cover grinding tool for vibration forming; the observation hole cover is naturally cured for 3 days and can be put into use after being naturally cooled; the castable disclosed by the invention is low in heat conductivity coefficient, so that the heat loss in the coke oven is greatly reduced; the castable is low in density, light in weight, convenient to operate, wide in castable source and low in price.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials for coke ovens in the steel industry, and in particular to a lightweight thermal insulation castable for a coke oven fire viewing hole cover and a preparation and use method thereof. Background Art

[0002] Coke ovens are complex large-scale industrial kilns, usually made of refractory bricks and refractory blocks. They use coal to make coke and are the main thermal equipment for coking. The fire hole is an important part of the coke oven. It is installed at the mouth of the vertical fire channel. The fire hole of the coke oven is mainly used for ventilation and monitoring the thermal state of coke. When measuring the temperature of the coke oven, the fire hole cover needs to be opened and then closed. At present, the fire hole cover used in domestic coke ovens is generally cast in one piece using ordinary cast iron. This kind of fire hole cover has a large thermal conductivity. A large amount of heat from the vertical fire channel dissipates to the surface environment of the coke oven top through the fire hole cover, which not only causes energy waste, but also worsens the working environment of the coke oven top. In order to enhance the thermal insulation effect of the fire hole cover, reduce the heat dissipation of the furnace top and improve the thermal efficiency, in recent years, scientific researchers have re-optimized the structure of the fire hole cover, but it is still made of cast iron, and the effect is not obvious.

[0003] In view of the existing problems, the purpose of the present invention is to provide a lightweight heat-insulating refractory castable without changing the structure of the fire-viewing hole cover, to replace the existing cast iron material, and greatly improve its energy-saving effect. At the same time, the service life is not less than that of the original material fire-viewing hole cover, so as to solve the problem that the existing cast iron fire-viewing hole cover has poor insulation effect, causing heat dissipation and energy waste. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a lightweight thermal insulation castable for a coke oven fire hole cover and a preparation and use method thereof. The lightweight thermal insulation castable for a coke oven fire hole cover has low cost and excellent performance, low thermal conductivity, low price, light weight and is easy to operate.

[0005] The technical solution adopted by the present invention to solve its technical problem is: a lightweight thermal insulation castable for a coke oven fire-viewing hole cover, comprising a main material, a binder and a pore-forming agent, wherein the main material comprises calcium hexaaluminate, mullite, kyanite, high-alumina bauxite, zircon, high-boron calcium borate and SnO2, the binder comprises magnesium chloride and PVAC, and the pore-forming agent adopts an AC foaming agent.

[0006] Specifically, the raw material components of the main material, binder and pore-forming agent include:

[0007] The weight percentage of calcium hexaaluminate is 12%-34%, and the particle size distribution is 3mm-5mm;

[0008] The weight percentage of mullite is 15%-30%, and the particle size distribution is 1mm-3mm;

[0009] The weight percentage of kyanite is 5%-15%, and the particle size distribution is 1mm-3mm;

[0010] The weight percentage of high-alumina bauxite is 10%-15%, and the particle size distribution is 1mm-2mm;

[0011] The weight percentage of zircon is 4%-9%, and the particle size distribution is 0mm-1mm;

[0012] The weight percentage of high boron calcium borate is 5%-10%, and the particle size distribution is <0.088mm;

[0013] The weight percentage of SnO2 is 6%-10%, and the particle size distribution is <30um;

[0014] The weight percentage of magnesium chloride is 3%-5%, and the particle size distribution is 180 mesh;

[0015] The weight percentage of PVAC is 1%-3%;

[0016] The weight percentage of AC foaming agent is 1%-3%, and the particle size distribution is 200 mesh.

[0017] Furthermore, the raw material components of the main material, binder and pore-forming agent specifically include:

[0018] The weight percentage of calcium hexaaluminate is 17%-25%, and the particle size distribution is 3mm-5mm;

[0019] The weight percentage of mullite is 19%-23%, and the particle size distribution is 1mm-3mm;

[0020] The weight percentage of kyanite is 8%-12%, and the particle size distribution is 1mm-3mm;

[0021] The weight percentage of high-alumina bauxite is 12%-15%, and the particle size distribution is 1mm-2mm;

[0022] The weight percentage of zircon is 5%-8%, and the particle size distribution is 0mm-1mm;

[0023] The weight percentage of high boron calcium borate is 5%-9%, and the particle size distribution is <0.088mm;

[0024] The weight percentage of SnO2 is 7%-10%, and the particle size distribution is <30um;

[0025] The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh;

[0026] The weight percentage of PVAC is 1%-3%;

[0027] The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

[0028] Furthermore, the raw material components of the main material, binder and pore-forming agent specifically include:

[0029] The weight percentage of calcium hexaaluminate is 22%-24%, and the particle size distribution is 3mm-5mm;

[0030] The weight percentage of mullite is 20%-23%, and the particle size distribution is 1mm-3mm;

[0031] The weight percentage of kyanite is 9%-11%, and the particle size distribution is 1mm-3mm;

[0032] The weight percentage of high-alumina bauxite is 12%-14%, and the particle size distribution is 1mm-2mm;

[0033] The weight percentage of zircon is 6%-7%, and the particle size distribution is 0mm-1mm;

[0034] The weight percentage of high boron calcium borate is 5%-8%, and the particle size distribution is <0.088mm;

[0035] The weight percentage of SnO2 is 8%-10%, and the particle size distribution is <30um;

[0036] The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh;

[0037] The weight percentage of PVAC is 2%-3%;

[0038] The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

[0039] Furthermore, the raw material components of the main material, binder and pore-forming agent specifically include:

[0040] The weight percentage of calcium hexaaluminate is 23%-24%, and the particle size distribution is 3mm-5mm;

[0041] The weight percentage of mullite is 21%-22%, and the particle size distribution is 1mm-3mm;

[0042] The weight percentage of kyanite is 9%-10%, and the particle size distribution is 1mm-3mm;

[0043] The weight percentage of high-alumina bauxite is 12%-13%, and the particle size distribution is 1mm-2mm;

[0044] The weight percentage of zircon is 6%-7%, and the particle size distribution is 0mm-1mm;

[0045] The weight percentage of high boron calcium borate is 6%-7%, and the particle size distribution is <0.088mm;

[0046] The weight percentage of SnO2 is 8%-9%, and the particle size distribution is <30um;

[0047] The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh;

[0048] The weight percentage of PVAC is 2%-3%;

[0049] The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

[0050] A preparation and use method of a lightweight thermal insulation castable for a coke oven fire hole cover comprises the following steps:

[0051] S1. Weigh the raw material components of the main material, binder and pore-forming agent in proportion, and mix and stir for 6-10 minutes;

[0052] S2, adding 10%-15% of the total weight of the mixture of water, continue mixing and stirring for 7-9 minutes to obtain a castable;

[0053] S3, injecting the castable into the fixed fire hole cover mold and vibrating it to form the fire hole cover;

[0054] S4. The fire hole cover cast in step 3) is naturally cured for 3 days, baked at 120° C. for 48 hours, and then kept warm at 1200° C. in a high-temperature furnace for 24 hours. It can be put into use after natural cooling.

[0055] The present invention has the following beneficial effects:

[0056] The invention discloses a lightweight heat-insulating castable for a coke oven fire-viewing hole cover and a preparation and use method thereof. The castable has a low thermal conductivity, which reduces the surface temperature of the hole cover from more than 230°C to less than 70°C, thereby greatly reducing the heat loss inside the coke oven.

[0057] The lightweight heat-insulating castable designed by the invention for the coke oven fire-viewing hole cover and the preparation and use method thereof have low density and light weight. The weight of one cover is reduced from 2.2 kg to 0.8 kg, which is convenient for operation.

[0058] The invention discloses a lightweight heat-insulating castable for a coke oven fire-viewing hole cover and a preparation method and a use method thereof. The castable has a wide source and is cheap. DETAILED DESCRIPTION

[0059] The technical solutions in the embodiments of the present invention are described in detail below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] A lightweight thermal insulation castable for a coke oven fire-viewing hole cover and a preparation and use method thereof. The raw material component formula table of Examples 1-7 is shown in Table 1 below:

[0061] Table 1 The raw material composition formula of Examples 1-7, unit: weight percentage (%).

[0062]

[0063] The term “0 mm” in the particle size distribution range does not include 0 mm, and means that the particle size distribution range is larger than 0 mm.

[0064] Example 1: A lightweight thermal insulation castable for a coke oven fire hole cover and a preparation and use method thereof, the raw material formula of which is shown in Table 1:

[0065] 1) Weigh the raw material components of the main material, binder and pore-forming agent in proportion, mix and stir for 6 to 10 minutes;

[0066] 2) Add 10% to 15% of the total weight of the mixture into water, and continue mixing and stirring for 7 to 9 minutes to obtain a castable.

[0067] The present invention also provides a method for using the above-mentioned castable, comprising the following steps:

[0068] 1) injecting the casting material into the fixed fire hole cover mold and vibrating and forming it to obtain the fire hole cover;

[0069] 2) The fire hole cover cast in step 1) is naturally cured for 3 days, baked at 120° C. for 48 hours, and then kept at 1200° C. in a high-temperature furnace for 24 hours, and then put into use after natural cooling.

[0070] Its main physical and chemical indicators are as follows:

[0071]

[0072] Example 2: A lightweight thermal insulation castable for a coke oven fire hole cover, the raw material formula of which is shown in Table 1:

[0073] The preparation and use methods of the castable are the same as those in Example 1, and its main physical and chemical indicators are as follows:

[0074]

[0075]

[0076] Example 3: A lightweight heat-insulating castable for a coke oven fire-viewing hole cover, the raw material formula of which is shown in Table 1: The preparation and use methods of the castable are the same as those of Example 1, and its main physical and chemical indicators are as follows:

[0077]

[0078] Example 4: A lightweight heat-insulating castable for a coke oven fire-viewing hole cover, the raw material formula of which is shown in Table 1: The preparation and use methods of the castable are the same as those of Example 1, and its main physical and chemical indicators are as follows:

[0079]

[0080] Example 5: A lightweight heat-insulating castable for a coke oven fire-viewing hole cover, the raw material formula of which is shown in Table 1: The preparation and use methods of the castable are the same as those of Example 1, and its main physical and chemical indicators are as follows:

[0081]

[0082] Example 6: A lightweight heat-insulating castable for a coke oven fire-viewing hole cover, the raw material formula of which is shown in Table 1: The preparation and use methods of the castable are the same as those of Example 1, and its main physical and chemical indicators are as follows:

[0083]

[0084] Example 7: A lightweight thermal insulation castable for a coke oven fire hole cover, the raw material formula of which is shown in Table 1: The preparation and use methods of the castable are the same as those of Example 1, and its main physical and chemical indicators are as follows:

[0085]

[0086] 1. Compared with the existing cast iron fire hole cover, the castable has a low thermal conductivity, which reduces the surface temperature of the hole cover from more than 230°C to less than 70°C, greatly reducing the heat loss inside the coke oven.

[0087] 2. Compared with the existing cast iron fire hole cover, the castable has low density and light weight. The weight of a cover is reduced from the original 2.2 kg to 0.8 kg, which is easy to operate.

[0088] 3. Compared with the existing cast iron fire hole cover, this castable has a wide source and is cheap.

[0089] 4. The cast quality fire hole cover can meet the use conditions of the coke oven roof. Its main physical and chemical indicators are as follows:

[0090]

[0091] Refractory temperature (℃) The refractoriness of the sample is tested according to GB / T 7322-2007.

[0092] Bulk density (g / cm 3 ) The bulk density of the sample is tested according to GB / T 2007.7-1987.

[0093] Compressive Strength (MPa) The compressive strength and bonding strength of the samples are tested according to GB / T 3001-2007.

[0094] Thermal conductivity (W / m·℃) The thermal conductivity of the sample was tested according to GB / T 5990-2006.

[0095] Thermal shock stability (times) According to YB / T 376-1995, the thermal shock stability of the sample is tested.

[0096] The present invention is not limited to the above-mentioned implementation modes, and anyone should be aware of the structural changes made under the enlightenment of the present invention, and all those having the same or similar technical solutions as the present invention fall within the protection scope of the present invention.

[0097] The techniques, shapes, and structural parts not described in detail in the present invention are all well-known techniques.

Claims

1. A lightweight thermal insulation castable for a coke oven fire hole cover, characterized in that: The invention comprises a main material, a binder and a pore-forming agent. The main material comprises calcium hexaaluminate, mullite, kyanite, high-alumina bauxite, zircon, high-boron calcium borate and SnO2. The binder comprises magnesium chloride and PVAC. The pore-forming agent adopts AC foaming agent.

2. The lightweight thermal insulation castable for the coke oven fire hole cover according to claim 1, characterized in that: The raw material components of the main material, binder and pore-forming agent specifically include: The weight percentage of calcium hexaaluminate is 12%-34%, and the particle size distribution is 3mm-5mm; The weight percentage of mullite is 15%-30%, and the particle size distribution is 1mm-3mm; The weight percentage of kyanite is 5%-15%, and the particle size distribution is 1mm-3mm; The weight percentage of high-alumina bauxite is 10%-15%, and the particle size distribution is 1mm-2mm; The weight percentage of zircon is 4%-9%, and the particle size distribution is 0mm-1mm; The weight percentage of high boron calcium borate is 5%-10%, and the particle size distribution is <0.088mm; The weight percentage of SnO2 is 6%-10%, and the particle size distribution is <30um; The weight percentage of magnesium chloride is 3%-5%, and the particle size distribution is 180 mesh; The weight percentage of PVAC is 1%-3%; The weight percentage of AC foaming agent is 1%-3%, and the particle size distribution is 200 mesh.

3. The lightweight thermal insulation castable for the coke oven fire hole cover according to claim 2, characterized in that: The raw material components of the main material, binder and pore-forming agent specifically include: The weight percentage of calcium hexaaluminate is 17%-25%, and the particle size distribution is 3mm-5mm; The weight percentage of mullite is 19%-23%, and the particle size distribution is 1mm-3mm; The weight percentage of kyanite is 8%-12%, and the particle size distribution is 1mm-3mm; The weight percentage of high-alumina bauxite is 12%-15%, and the particle size distribution is 1mm-2mm; The weight percentage of zircon is 5%-8%, and the particle size distribution is 0mm-1mm; The weight percentage of high boron calcium borate is 5%-9%, and the particle size distribution is <0.088mm; The weight percentage of SnO2 is 7%-10%, and the particle size distribution is <30um; The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh; The weight percentage of PVAC is 1%-3%; The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

4. The lightweight heat-insulating castable for the coke oven fire-viewing hole cover according to claim 3, characterized in that: The raw material components of the main material, binder and pore-forming agent specifically include: The weight percentage of calcium hexaaluminate is 22%-24%, and the particle size distribution is 3mm-5mm; The weight percentage of mullite is 20%-23%, and the particle size distribution is 1mm-3mm; The weight percentage of kyanite is 9%-11%, and the particle size distribution is 1mm-3mm; The weight percentage of high-alumina bauxite is 12%-14%, and the particle size distribution is 1mm-2mm; The weight percentage of zircon is 6%-7%, and the particle size distribution is 0mm-1mm; The weight percentage of high boron calcium borate is 5%-8%, and the particle size distribution is <0.088mm; The weight percentage of SnO2 is 8%-10%, and the particle size distribution is <30um; The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh; The weight percentage of PVAC is 2%-3%; The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

5. The lightweight heat-insulating castable for the coke oven fire-viewing hole cover according to claim 4, characterized in that: The raw material components of the main material, binder and pore-forming agent specifically include: The weight percentage of calcium hexaaluminate is 23%-24%, and the particle size distribution is 3mm-5mm; The weight percentage of mullite is 21%-22%, and the particle size distribution is 1mm-3mm; The weight percentage of kyanite is 9%-10%, and the particle size distribution is 1mm-3mm; The weight percentage of high-alumina bauxite is 12%-13%, and the particle size distribution is 1mm-2mm; The weight percentage of zircon is 6%-7%, and the particle size distribution is 0mm-1mm; The weight percentage of high boron calcium borate is 6%-7%, and the particle size distribution is <0.088mm; The weight percentage of SnO2 is 8%-9%, and the particle size distribution is <30um; The weight percentage of magnesium chloride is 3%-4%, and the particle size distribution is 180 mesh; The weight percentage of PVAC is 2%-3%; The weight percentage of AC foaming agent is 2%-3%, and the particle size distribution is 200 mesh.

6. The method for preparing and using the lightweight thermal insulation castable for the coke oven fire hole cover according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh the raw material components of the main material, binder and pore-forming agent in proportion, and mix and stir for 6-10 minutes; S2, adding 10%-15% of the total weight of the mixture of water, continue mixing and stirring for 7-9 minutes to obtain a castable; S3, injecting the castable into the fixed fire hole cover mold and vibrating it to form the fire hole cover; S4. The fire hole cover cast in step 3) is naturally cured for 3 days, baked at 120° C. for 48 hours, and then kept warm at 1200° C. in a high-temperature furnace for 24 hours. It can be put into use after natural cooling.

Citation Information

Patent Citations

  • Fire-retardant aerated brick

    CN104987089A

  • Ultra-high strength lightweight heat insulating brick for roasting furnace and preparation method thereof

    CN108997026A

  • Light thermal insulation castable for coke oven coal charging hole cover, preparation method and use method thereof

    CN111018551A

  • Anti-radiation heat insulation screen and preparation method thereof

    CN114656266A

  • Material-resistant coke pot lining repairing material as well as preparation method and use method thereof

    CN117586028A